(untitled) (World of finance, 2019)
Introduction. In the conditions of the implementation of the government’s decentralization reform, local communities received the real opportunities for increasing the resources which can be used for development. One of the conditions, which provides their economic development, is to create an effective system of intergovernmental relations, aimed to optimizing fiscal decentralization and clear definition of the powers of local government. The increasing interest to the problem of expanding of local communities financial capacity caused by the necessity to find improved mechanisms for incomes separation between the elements of the budget system and types of budgets. Purpose. The purpose of this article is to study of intergovernmental relations in the context of achieving financial viability of local communities and to summarize the preliminary results of the reform. Results. The features of intergovernmental relations in local government reform in Ukraine are highlighted. The fiscal innovations, which extends the autonomy principles of local budgets, reallocates expenditure responsibilities between levels of government and creates conditions for intensification of the process of voluntary association of municipalities, have been analyzed. The first phase of fiscal decentralization in Ukraine has been estimated. It has been shown that despite the strengthening of the solvency of local budgets, the negative trends is intensified: excessive centralization of budgetary decisions; imperfect distribution of functional responsibilities and rights between the central and local governments; low human resource capacity of the community; low financial autonomy of local government and so on. The risks of the further deepening the fiscal decentralization have been justified. Conclusions. It was suggested the directions for increasing financial capacity of local communities in the introduction of industry standards of public services, which should increase the efficiency of planning and using of public funds at all levels; in the improving the basic and reverse subsidies calculations and in the estimation the risks of the fiscal decentralization.